Poly I:C and STING agonist‐primed DC increase lymphoid tissue polyfunctional HIV‐1‐specific CD8+ T cells and limit CD4+ T‐cell loss in BLT mice. Issue 3 (8th January 2022) - Calvet‐Mirabent, Marta; Claiborne, Daniel T.; Deruaz, Maud; Tanno, Serah; Serra, Carla; Delgado‐Arévalo, Cristina; Sánchez‐Cerrillo, Ildefonso; de los Santos, Ignacio; Sanz, Jesús; García‐Fraile, Lucio; Sánchez‐Madrid, Francisco; Alfranca, Arantzazu; et al.
Abstract: Effective function of CD8 + T cells and enhanced innate activation of DCs in response to HIV‐1 is linked to protective antiviral immunity in controllers. Manipulation of DC targeting the master regulator TANK‐binding Kinase 1 (TBK1) might be useful to acquire controller‐like properties. Here, we evaluated the impact of the combination of 2´3´‐c´diAM(PS)2 and Poly I:C as potential adjuvants capable of potentiating DC´s abilities to induce polyfunctional HIV‐1 specific CD8 + T‐cell responses in vitro and in vivo using a humanized BLT mouse model. Adjuvant combination enhanced TBK‐1 phosphorylation and IL‐12 and IFN‐β expression on DC and increased their ability to activate polyfunctional HIV‐1‐specific CD8 + T cells in vitro . Moreover, higher proportions of hBLT mice vaccinated with ADJ‐DC exhibited less severe CD4 + T‐cell depletion following HIV‐1 infection compared to control groups. This was associated with infiltration of CD8 + T cells in the white pulp from the spleen, reduced spread of infected p24 + cells to LN, and with preserved abilities of CD8 + T cells from the spleen and blood of vaccinated animals to induce specific polyfunctional responses upon antigen stimulation. Therefore, priming of DC with PolyI:C and STING agonists might be useful for future HIV‐1 vaccine studies. Abstract : Vaccination of humanized BLT mice with DCs primed with 2'3'‐c'diAM(PS)2 and Poly I:C increased infiltration and polyfunctionality of HIV‐1‐specific CD8+ T cells into the spleen white pulp, reduced spread of infection to the LN, and less severe CD4+ T‐cell depletion after HIV‐1 infection.